Una aproximación a la crónica /crítica literaria - Forneas Fernández, María Celia (Estudios sobre el Mensaje Periodístico, 2006)
The discipline known as literary critic and its development in the field of the culture is, on my honest opinion, a Gordian knot that nobody has been able to cut up. At the present time, we fundamentally deal with academical literary critic and the journalistic literary chronicle; I insist : jounalistic literary chronicle because it is the only reasonable denomination that can be applied to book lectures, cinematographic and television reviews, and the other cultural events transmitted by mass communication means as newsreel. In addition, the Spanish literary scene has enormeously changed in the last thirty years. Due to the increase of publications in catalan, galician and basque, Spain is now a coutry with four literary languages.Today, the importance of these languages is dissmilar but we do not know what will happen in the future.